Emerging Modulators of TMEM16A and Their Therapeutic Potential - Hao, Anqi; Guo, Shuai; Shi, Sai; Wang, Xuzhao; Zhan, Yong; Chen, Yafei; An, Hailong (The Journal of membrane biology, 2021)
Calcium-activated chloride channels (CaCCs) are widespread chloride channels which rely on calcium activation to perform their functions. In 2008, TMEM16A (also known as anoctamin1, ANO1) was identified as the molecular basis of the CaCCs, which provided the possibility to study the physiological function of CaCCs. TMEM16A is widely expressed in various cells and controls basic physiological functions, including neuronal and cardiac excitability, nerve transduction, smooth muscle contraction, epithelial Cl − secretion and fertilization. However, the abnormal function of TMEM16A may cause a variety of diseases, including asthma, gastrointestinal motility disorder and various cancers. Therefore, TMEM16A is a putative drug target for many diseases, and it is important to determine specific and efficient modulators of TMEM16A channel. In recent years, we and others have screened several natural modulators of TMEM16A against cancers and gastrointestinal motility dysfunction. This article reviews the screening methods, efficacy of TMEM16A modulators and pharmacological effects of TMEM16A modulators on different diseases. Graphic Abstact